Heading incidence and characteristics in elite women's football over the 2020/2021 season - Bentley, L.; Lauder, M.; Smith, N. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of the study was to analyse the magnitude of head impact incidence and heading characteristics in elite women`s football across a season. Football players (matches n=25, training n=18) had their headers and head impacts quantified and characterised for the 2020/2021 season. Video recordings from a single elevated camera on the halfway line was used to analyse for 22 matches and 98 training sessions. Overall, 5063 headers and 9 non-ball to head impacts were collected and analysed. This study shows more headers occurred in training than matches for the team of interest across the season (training, 2976; matches, 974). However, the nature of the headers was more submaximal in training than matches, the rate of headers was lower (training, 15.9 headers per hour; matches 29.5 headers per hour), and non-ball to head impacts were much lower (training, 0; matches 9). The longitudinal study presents differences between headers and head impacts in matches and training and provides novel data to further develop our understanding of heading in women`s football.